Patient expertise: Contested territory in the realm of long-term condition care. (September 2019) - Francis, Helen; Carryer, Jenny; Wilkinson, Jill
Objectives: The aim of this study was to describe the experience of people with multiple long-term conditions with particular reference to the notion of the 'expert patient' in the context of self-management. Methods: A multiple case study of 16 people with several long-term conditions, included interviews and contacts over an 18-month period and an interview with their primary care clinicians. Analysis included both case-by-case and some cross-case analysis. Results: The findings reveal the patient participants had little capacity to exercise the agency necessary be an expert patient as premised. Weariness, shame, expertise, issues of compliance and control and collaboration are contested areas underpinning clinician encounters. Discussion: Patient expertise is at the heart of self-management approaches but the findings surfaced several inherent contradictions between the idealised expert patient and their position within a health care system that is entrenched in biomedicine. Conclusion: There is a mismatch between how the self-management approach has been operationalised and what the participants who have multiple LTCs reveal as what they want and need. The research concludes that the self-management approach is inappropriate for people with multiple LTCs and that other ways of offering care should be considered.